Bacillus subtilis natto Derivatives Inhibit Enterococcal Biofilm Formation via Restructuring of the Cell Envelope - Lin, Yu-Chieh; Wu, Chun-Yi; Huang, Hung-Tse; Lu, Mei-Kuang; Hu, Wei-Shou; Lee, Kung-Ta (Frontiers in Microbiology, 2021)
Enterococcus faecalis is considered a leading cause of hospital-acquired infections. Treatment of these infections has become a major challenge for clinicians because some E. faecalis strains are resistant to multiple clinically used antibiotics. Moreover, the presence of E. faecalis biofilms can make infections with E. faecalis more difficult to eradicate with current antibiotic therapies. Thus, our aim in this study was to investigate the effects of probiotic derivatives against E. faecalis biofilm formation. Bacillus subtilis natto is a probiotic strain isolated from Japanese fermented soybean foods, and its culture fluid potently inhibited adherence to Caco-2 cell monolayers, aggregation, and biofilm production without inhibiting the growth of E. faecalis. An apparent decrease in the thickness of E. faecalis biofilms was observed through confocal laser scanning microscopy. In addition, exopolysaccharide synthesis in E. faecalis biofilms was reduced by B. subtilis natto culture fluid treatment. Carbohydrate composition analysis also showed that carbohydrates in the E. faecalis cell envelope were restructured. Furthermore, transcriptome sequencing revealed that the culture fluid of B. subtilis natto downregulated the transcription of genes involved in the WalK/WalR two-component system, peptidoglycan biosynthesis and membrane glycolipid biosynthesis, which are all crucial for E. faecalis cell envelope synthesis and biofilm formation. Collectively, our work shows that some derivatives present in the culture fluid of B. subtilis natto may be useful for controlling E. faecalis biofilms.